Tracking India’s progress on addressing malnutrition: What will it take? - Menon, Purnima; Avula, Rasmi; Sarswat, Esha; Mani, Sneha; Jangid, Manita; Singh, Anamika; Kaur, Supreet; Dubey, Alok Kumar; Gupta, Shuchita; Nair, Divya; Agarwal, Pulkit; Agrawal, Nitya (International Food Policy Research Institute, 2020)
India has a robust policy framework for nutrition that covers most evidence-based interventions (Vir et al. 2013), and it has in place large-scale national program platforms – the Integrated Child Development Services and the National Rural Health Mission – with the mandate to deliver diverse nutrition interventions (Avula et al. 2013). The National Nutrition Strategy (NITI Aayog 2017) and POSHAN Abhiyaan, India’s national nutrition mission launched in early 2018, provide an updated strategic framework for action to improve nutritional outcomes for children, pregnant women, and lactating mothers. The mission-mode approach provides an impetus to strengthen not only the implementation but also the monitoring and measurement of progress. The mission explicitly notes that NITI Aayog has a mandate to lead on the monitoring and evaluation of POSHAN Abhiyaan. This Policy Note, developed jointly with NITI Aayog and IDinsight, aims to provide guidance to national, state, and district level government officials/stakeholders on issues to consider on the use of data to track progress on nutrition interventions, immediate and underlying determinants, and outcomes. It proposes an indicator framework for POSHAN Abhiyaan and examines availability of data on these indicators across both population-based surveys and administrative data systems. Finally, it lays out issues to be considered in strengthening efforts to improve the use of data in the context of POSHAN Abhiyaan and makes key recommendations on improving data availability and improving the use of currently available data.